Atmospheric CH4 oxidation by Arctic permafrost and mineral cryosols as a function of water saturation and temperature. Issue 1 (29th July 2016) - Stackhouse, B.; Lau, M. C. Y.; Vishnivetskaya, T.; Burton, N.; Wang, R.; Southworth, A.; Whyte, L.; Onstott, T. C.
Abstract: The response of methanotrophic bacteria capable of oxidizing atmospheric CH4 to climate warming is poorly understood, especially for those present in Arctic mineral cryosols. The atmospheric CH4 oxidation rates were measured in microcosms incubated at 4 °C and 10 °C along a 1‐m depth profile and over a range of water saturation conditions for mineral cryosols containing type I and type II methanotrophs from Axel Heiberg Island (AHI), Nunavut, Canada. The cryosols exhibited net consumption of ~2 ppmv CH4 under all conditions, including during anaerobic incubations. Methane oxidation rates increased with temperature and decreased with increasing water saturation and depth, exhibiting the highest rates at 10 °C and 33% saturation at 5 cm depth (260 ± 60 pmol CH4 gdw −1 d −1 ). Extrapolation of the CH4 oxidation rates to the field yields net CH4 uptake fluxes ranging from 11 to 73 μmol CH4  m −2 d −1, which are comparable to field measurements. Stable isotope mass balance indicates ~50% of the oxidized CH4 is incorporated into the biomass regardless of temperature or saturation. Future atmospheric CH4 uptake rates at AHI with increasing temperatures will be determined by the interplay of increasing CH4 oxidation rates vs. water saturation and the depth to the water table during summer thaw.